Policy and decision making in education during the Covid-19 Pandemic: A Case Study of SMAN 1 Rupat - Sumantri, Pulung; Hasudungan, Anju Nofarof (International Journal for Educational and Vocational Studies)
This study aims to describe the educational policies issued by the Ministry of Education, Culture, Research and Technology and the decisions taken by Senior High School 1 Rupat (SMAN 1 Rupat) as an effort to continue education during the Covid-19 pandemic. The research method used is descriptive qualitative research method with a case study approach. Data was collected by means of literature study, interviews, documents and observations. Data analysis was carried out by adopting an interactive model from Miles and Huberman. The results of the study show that flexibility is the goal of the issuance of policies and decisions taken by the government and schools with the aim of maintaining student safety from Covid-19 and minimizing the impact of learning loss. The challenge in the future is to find a model of resilience that can be maximized to restore Indonesian education.